2018
DOI: 10.2147/jaa.s136417
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of smoke exposure on airway and systemic inflammation in forest firefighters

Abstract: IntroductionThe aim of this study was to assess respiratory health and airway and systemic inflammation in professional forest firefighters post firefighting.MethodsA total of 60 firefighters who participated in forest firefighting operations in Greece during 2008 were included in the study. A questionnaire consisting of symptoms and exposure, pulmonary function, atopy, bronchial hyperresponsiveness, and markers of inflammation in induced sputum, serum, and bronchoalveolar lavage (BAL) fluid was assessed.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
(66 reference statements)
0
15
0
Order By: Relevance
“…Twelve academic articles reported on inflammation and oxidative stress related outcomes [ 5 , 20 , 92 , 93 , 95 – 102 ]. Studies reported an increase in airway and systemic inflammation after acute exposure to wildland fire [ 96 ]. This includes increases in IL-6 and IL-8 in field [ 96 , 97 ] and at prescribed burn shifts [ 92 ], and decreases in IL-10 after 12 h (post-shift) of fire suppression [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve academic articles reported on inflammation and oxidative stress related outcomes [ 5 , 20 , 92 , 93 , 95 – 102 ]. Studies reported an increase in airway and systemic inflammation after acute exposure to wildland fire [ 96 ]. This includes increases in IL-6 and IL-8 in field [ 96 , 97 ] and at prescribed burn shifts [ 92 ], and decreases in IL-10 after 12 h (post-shift) of fire suppression [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies reported an increase in airway and systemic inflammation after acute exposure to wildland fire [ 96 ]. This includes increases in IL-6 and IL-8 in field [ 96 , 97 ] and at prescribed burn shifts [ 92 ], and decreases in IL-10 after 12 h (post-shift) of fire suppression [ 97 ]. At prescribed burns, there was no association between dose of PM 2.5 (based on fireline task exposure) and inflammatory biomarkers [ 92 ], although an exposure-response relationship was observed between a black carbon measure and inflammation [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…This analysis indicated that the post-fire period had a detectable statistically significant deficit in delta_PF and that the post-fire period, which was one-year after the wildfire event, could be impacted. This is conceivable as there are a number of reports in the literature that demonstrated that it may be possible for ambient air pollution, and wildfire smoke specifically, to act as an adjuvant to a delayed allergic sensitization of the respiratory system [22][23][24][25][26][27][28][29][30][31]. Therefore, the allergy patients attending this clinic may have become more susceptible and experienced more significant changes in peak flow associated with their allergic rhinitis and asthma as a result of their wildfire smoke exposure, and this was detected one year after the wildfire event.…”
Section: Discussionmentioning
confidence: 99%
“…Disaster Medicine and Public Health Preparedness smoke, ash, disturbed soil, and other chemical emissions from burning or smoldering structures, vehicles, and brush may also have contributed to respiratory irritation among these first responders. [17][18][19][20][21][22][23][24] Given the high proportion of responders reporting acute and ongoing post-response health symptoms and the potential for toxic exposures, responders should be encouraged to seek post-response medical care or evaluation. Barriers to seeking care should be identified and addressed to promote post-response health care.…”
Section: Discussionmentioning
confidence: 99%